Multiplex lateral flow detection and binary encoding enables a molecular colorimetric 7-segment display. Issue 2 (1st December 2015) - Li, Jia; Macdonald, Joanne
Abstract : First proof-of-concept generic 7-segment display for a lateral flow biosensor, with exponential multiplexing detection ability via a binary encoding concept. Abstract : Multiplex expansion in point-of-care diagnostics usually requires a linear increase of premium commodities such as reagents or space. Here we demonstrate the power of binary and molecular encoding to compress device operations. We describe the first colorimetric 7-segment display on a paper-based biosensor, providing compact and intuitive read-outs for multiplex detections.